The Effect of Plastic Deformation on the Geometric Parameters of Nb-Ti-Based Superconducting Cable; IOP Conference Series: Materials Science and Engineering; Vol. 731 : Advanced Materials for Engineering and Medicine (AMEM-2019) - Yntymakova A. (2020, 2020)
Title screen